Clinical Characteristics and Seizure Outcomes in Antibody-Positive Autoimmune Limbic Encephalitis - Song H; Xu S; Du BQ; Lai QL; Cai MT; Li H; Hu Y; Ding Y; Ding MP; Zhang YX; Shen CH (Journal of Inflammation Research)
Hao Song,1,* Sha Xu,1,* Bing-Qing Du,1 Qi-Lun Lai,2 Meng-Ting Cai,1 Hong Li,3 Yin Hu,1 Yao Ding,1 Mei-Ping Ding,1 Yin-Xi Zhang,1 Chun-Hong Shen1 1Department of Neurology, Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, 310009, People’s Republic of China; 2Department of Neurology, Zhejiang Hospital, Hangzhou, 310013, People’s Republic of China; 3Department of Radiology, Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, 310009, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chun-Hong Shen, Department of Neurology, Second Affiliated Hospital, School of Medicine, Zhejiang University, 88 Jiefang Road, Hangzhou, 310009, People’s Republic of China, Email shen_neurology@zju.edu.cn Yin-Xi Zhang, Department of Neurology, Second Affiliated Hospital, School of Medicine, Zhejiang University, 88 Jiefang Road, Hangzhou, 310009, People’s Republic of China, Email zyx-neurology@zju.edu.cnPurpose: Autoimmune limbic encephalitis (ALE) often occurs with detectable neuronal antibodies, presenting with seizures as a prominent clinical manifestation. We aimed to investigate the clinical characteristics and seizure outcomes in a cohort with antibody-positive ALE.Methods: We consecutively recruited patients with antibody-positive ALE and new-onset seizures between July 2014 and February 2024. Their demographic, clinical, and paraclinical characteristics, and treatment were collected. Seizure outcomes during follow-up were evaluated respectively, as well as the associated risk factors.Results: Seventy-two patients were included, and the associated autoantibodies targeted the leucine-rich glioma-inactivated 1 (LGI1), gamma-aminobutyric acid type B receptor (GABABR), and glutamic acid decarboxylase 65 (GAD65). Secondarily generalized tonic-clonic seizures and focal non-motor seizures were the most prevalent seizure semiologies, and 28 (38.9%) patients exhibited multiple seizure types. Furthermore, among 54 patients with over two years of follow-up, 16 (29.6%) experienced intermittent seizures lasting for more than one year. Younger onset, specific antibodies, and multiple seizure types were correlated with the longer seizure duration (all P < 0.05). Six (11.1%) patients continued to have seizures even after two years of follow-up, comprising two with LGI1 and four with GAD65 antibodies. Female sex, younger onset, and specific antibody profiles were significantly associated with sustained seizures, indicating autoimmune-associated epilepsy (AAE, all P < 0.05).Conclusion: In patients with antibody-positive ALE, seizure outcomes appeared to change over an extended follow-up period, particularly in those with LGI1 and GABABR antibodies. Younger age at disease onset, female sex, and specific antibody profiles may be indicators of AAE.Keywords: autoimmune limbic encephalitis, antibody, autoimmune-associated epilepsy, multiple seizure types